METHOD FOR CALCULATING SUPPLY POWER DURING A TEMPERATURE SENSOR FAILURE - AHN, O YOUNG; PARK, HYUN SOO (2015)
A method for calculating power supply during the suspension of a temperature sensor by failure is disclosed. According to an embodiment of the present invention, the method for calculating power supply comprises the steps of: determining whether one temperature sensor of a plurality of temperature sensors for detecting the temperature of a high voltage battery has failed; setting an error of detected temperatures of the remaining temperature sensors if the one temperature sensor has failed; comparing the magnitude of the maximal temperature among detected temperatures of the remaining temperature sensors and the magnitude of the minimal temperature among the difference of the predetermined error and detected temperatures of the remaining temperature sensors; and determining the maximal setting temperature and the minimal setting temperature in accordance with the result of the comparison and calculating power supply supplied by the battery based on the maximal setting temperature and the minimal setting temperature. 온도 센서 고장 시 공급 파워 산출 방법이 개시된다. 본 발명의 실시 예에 따른 공급 파워 산출 방법은, 고전압 배터리의 온도를 검출하는 복수의 온도 센서 중 하나의 온도 센서가 고장임을 판단하는 단계; 상기 하나의 온도 센서가 고장인 경우, 나머지 온도 센서의 검출 온도의 오차를 설정하는 단계; 상기 나머지 온도 센서의 검출 온도 중 최대 온도와 상기 설정된 오차의 차와 상기 나머지 온도 센서의 검출 온도 중 최소 온도의 크기를 비교하는 단계; 및 상기 비교 결과에 따라 최대 설정 온도와 최소 설정 온도를 결정하고, 상기 결정된 최대 설정 온도와 최소 설정 온도에 기반하여 상기 배터리가 공급하는 공급 파워를 산출하는 단계를 포함할 수 있다.